Mechanical, antibacterial and bond strength properties of nano-titanium-enriched glass ionomer cement - Rene GARCIA-CONTRERAS; Rogelio Jose SCOUGALL-VILCHIS; Rosalía CONTRERAS-BULNES; Hiroshi SAKAGAMI; Raul Alberto MORALES-LUCKIE; Hiroshi NAKAJIMA (University of São Paulo, 2015)
The use of nanoparticles (NPs) has become a significant area of research in Dentistry. Objective The aim of this study was to investigate the physical, antibacterial activity and bond strength properties of conventional base, core build and restorative of glass ionomer cement (GIC) compared to GIC supplemented with titanium dioxide (TiO2) nanopowder at 3% and 5% (w/w). Material and Methods Vickers microhardness was estimated with diamond indenter. Compressive and flexural strengths were analyzed in a universal testing machine. Specimens were bonded to enamel and dentine, and tested for shear bond strength in a universal testing machine. Specimens were incubated with S. mutans suspension for evaluating antibacterial activity. Surface analysis of restorative conventional and modified GIC was performed with SEM and EDS. The analyses were carried out with Kolmogorov-Smirnov, ANOVA (post-hoc), Tukey test, Kruskal-Wallis, and Mann Whitney. Results Conventional GIC and GIC modified with TiO2 nanopowder for the base/liner cement and core build showed no differences for mechanical, antibacterial, and shear bond properties (p>0.05). In contrast, the supplementation of TiO2 NPs to restorative GIC significantly improved Vickers microhardness (p<0.05), flexural and compressive strength (p<0.05), and antibacterial activity (p<0.001), without interfering with adhesion to enamel and dentin. Conclusion GIC supplemented with TiO2 NPs (FX-II) is a promising material for restoration because of its potential antibacterial activity and durable restoration to withstand the mastication force.